The benefits of being an octopus - Braden, Ann (Sky Pony Press, 2018)
Seventh-grader Zoey looks after her much younger siblings after school in her mother's boyfriend's trailer house while her mother is working at the pizza parlor. Zoey and her friend Fuchia are the poor kids at school, and keep their heads and their problems down as much as they can--but Zoey cannot help wishing she were like an octopus, eight arms to do eight things all at once, with camouflage and great vision. Unfortunately, Zoey is not, and to make her life any better she will have to find her voice and face her problems.